2011
DOI: 10.3109/17549507.2011.632026
|View full text |Cite
|
Sign up to set email alerts
|

Living successfully with aphasia: A qualitative meta-analysis of the perspectives of individuals with aphasia, family members, and speech-language pathologists

Abstract: The concept of living successfully with aphasia has recently emerged as an alternative to more traditional "deficit" models in aphasiology, encouraging a focus on positive rather than negative outcomes. This research aimed to integrate findings from studies exploring the perspectives of three participant groups (individuals with aphasia, speech-language pathologists, and family members) about living successfully with aphasia. Qualitative meta-analysis of three studies conducted by the authors was used to integ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
94
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 148 publications
(100 citation statements)
references
References 55 publications
2
94
0
4
Order By: Relevance
“…The clinician perspectives were then included in a meta-analysis of perceptions of persons with aphasia and family members. 10 Although some perspectives were similar, the meta-analysis highlighted the different perspectives clinicians may have and the importance of exploring the perspectives of all stakeholders.…”
mentioning
confidence: 99%
“…The clinician perspectives were then included in a meta-analysis of perceptions of persons with aphasia and family members. 10 Although some perspectives were similar, the meta-analysis highlighted the different perspectives clinicians may have and the importance of exploring the perspectives of all stakeholders.…”
mentioning
confidence: 99%
“…Previous work has identified several overarching themes to successfully living with aphasia, which include; participation, meaningful relationships, support, communication, positivity, independence and autonomy, and succeeding as a journey over time (Brown, Worrall, Davidson & Howe, 2012). Some of these themes are evident in the experiences of these two individuals.…”
Section: Patterns In the Individual Performance Of Participants With mentioning
confidence: 99%
“…The importance of addressing the activity/participation level has been influenced by concepts embedded within the life participation approach and the challenge of living successfully with aphasia. 47, 48 Brown et al found that persons with aphasia reported several themes related to living successfully with aphasia, including the importance of meaningful relationships and its sub-themes of "acceptance and understanding" and "social companionship." 49 An ICAP addresses these sub-themes by bringing together a cohort, a group of participants who begin and end the program together.…”
Section: Comprehensiveness Of Aphasia Treatmentmentioning
confidence: 99%
“…Other qualitative and quantitative research has found that participants and family members endorse the importance of social networks and that a lack of social networks/support can lead to poor psychosocial health and poor quality of life. 12,48,68,117,172,193,194 …”
Section: Therapeutic Milieumentioning
confidence: 99%
See 1 more Smart Citation